2018
DOI: 10.1039/c8cp01020j
|View full text |Cite
|
Sign up to set email alerts
|

On the hydrogen evolution reaction activity of graphene–hBN van der Waals heterostructures

Abstract: Although graphene technology has reached technology readiness level 9 and hydrogen fuel has been identified as a viable futuristic energy resource, pristine atomic layers such as graphene are found to be inactive towards the hydrogen evolution reaction (HER). Enhancing the intrinsic catalytic activity of a material and increasing its number of active sites by nanostructuring are two strategies in novel catalyst development. Here, electrocatalytically inert graphene (G) and hexagonal boron nitride (hBN) are mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…HER is highly dependent on the pH of the electrolyte and it is facile at low pH (in acidic medium) due to the availability of proton for electro‐reduction. It is now clear that water electrolysis follows different mechanisms in acidic and alkaline media …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…HER is highly dependent on the pH of the electrolyte and it is facile at low pH (in acidic medium) due to the availability of proton for electro‐reduction. It is now clear that water electrolysis follows different mechanisms in acidic and alkaline media …”
mentioning
confidence: 99%
“…The proton or hydronium ions adsorption ( H abs ) on the active site is the first step in HER, and M−H (M stands for metal or other active sites) adsorption energy decides the activity of an electrocatalyst . For an ideal electrocatalyst, it has to be in thermoneutral, that is, Δ G H ∼0 eV – meaning adsorption and desorption (of H 2 ) energy should be optimum .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, such interfacing is found to be resulting in new solids of interesting electronic, optical, and electrochemical properties [30][31][32]. It is shown that even pristine graphene surfaces become electrochemically active while forming vdWs structures with MoS 2 and hBN [33,34]. Furthermore, vdWs structures of graphene with MoS 2 monolayers (MS) were found to provide enhanced hydrogen evolution catalytic activity compared with bare MS along with the enhanced stability even in harsh acid conditions and the interfacial charge transfer from graphene to MS was also established [35].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Hakim Faraji's team designed CuS‐ZrO 2 vdWs heterostructure material and found that it has a high absorption intensity in the uv range and has a promising future in the field of photocatalysis [13] . Based of g‐C 3 N 4 semiconductor heterostructure (the second type of heterojunction) photocatalyst has an appropriate band gap and a low degree of recombination of carriers and holes, which is very favorable for photocatalysis [14,15] . g‐C 3 N 4 has a relatively suitable E g ≈2.77 eV and CBM about −1 V, and its spectral absorption covers both ultraviolet and visible regions, and its electron reduction ability can meet the requirements of H 2 reduction [16] .…”
Section: Introductionmentioning
confidence: 99%